О методе сеток при решении обратных задач гравиметрии - Булах, Е.Г. (Видавничий дім "Академперіодика" НАН України, 2007)
The problem is reduced to solving the Fredholm integral equation. It is replaced by the system of linear equations and then by a specially constructed functional. Its minimization allows one to specify the position of bodies and their excessive density.